2005
DOI: 10.1002/lt.20469
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous ablation procedures in cirrhotic patients with hepatocellular carcinoma submitted to liver transplantation: Assessment of efficacy at explant analysis and of safety for tumor recurrence

Abstract: O rthotopic liver transplantation (OLT) is the ideal treatment for hepatocellular carcinoma (HCC) emerging in liver cirrhosis since both the tumor and the underlying cirrhosis can be cured. 1 According to Mazzaferro et al., 2 OLT should be restricted to patients with single HCC lower than 5 cm or with no more than 3 nodules, each smaller than 3 cm, in order to achieve an acceptable rate of tumor recurrence. Several studies confirmed a 5-year survival of 57 to 74% if these selection criteria are taken into acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
152
1
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(166 citation statements)
references
References 51 publications
7
152
1
6
Order By: Relevance
“…Previously, Kim et al 19 reported that a viable tumor volume ratio greater than 10% after preLT therapy was a significant prognostic factor. Pompili et al 20 also reported that 58.7% of HCC had partial necrosis after percutaneous ablation procedures and the effect depended on the size of HCCs. Also, Wong et al reported that fifteen nodules in five patients had <75% necrosis and these were due to local/non-local recurrences or perhaps suboptimal treatment with RFA, TACE or cisplatin gel injection.…”
Section: Discussionmentioning
confidence: 96%
“…Previously, Kim et al 19 reported that a viable tumor volume ratio greater than 10% after preLT therapy was a significant prognostic factor. Pompili et al 20 also reported that 58.7% of HCC had partial necrosis after percutaneous ablation procedures and the effect depended on the size of HCCs. Also, Wong et al reported that fifteen nodules in five patients had <75% necrosis and these were due to local/non-local recurrences or perhaps suboptimal treatment with RFA, TACE or cisplatin gel injection.…”
Section: Discussionmentioning
confidence: 96%
“…These studies show that complete tumor necrosis (evaluated on the explanted liver) may be achieved in 47-75% of the cases with a mean value of 58% [25][26][27][28][29]. A clear different effectiveness can be demonstrated analysing tumors of different size.…”
Section: Radiofrequency Thermal Ablationmentioning
confidence: 90%
“…A clear different effectiveness can be demonstrated analysing tumors of different size. In fact, the rate of complete necrosis ranges between 50% and 78% in tumors up to 3 cm and between 13% and 43% in larger tumors [25][26][27]29]. Furthermore, a tumor size exceeding 3 cm resulted the only risk factor for HCC persistence after treatment in two studies [25,27].…”
Section: Radiofrequency Thermal Ablationmentioning
confidence: 98%
See 1 more Smart Citation
“…This view is also in accordance with the fact that molecular analysis of the nontumorous liver parenchyma is predictive of such recurrences conversely to molecular analysis of the removed tumor. 6 In such a setting, it is clear that only transplantation could be called "curative", but in the numerous patients who are not eligible for such a procedure, the advantages of RFA over surgery are impressive: (1) RFA has lesser morbidity and mortality and is more comfortable for HEPATOLOGY, Vol. 51, No.…”
mentioning
confidence: 99%